Phenomena Of Religious Diversity Among Generation Z Students Study Of Religions Faculty Of Ushuluddin And Islamic Studies State Islamic University Of North Sumatra - Tasya Amanda; Indra Harahap (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
This research is motivated by the phenomenon of religious diversity among Generation Z students who live amidst the development of digital technology, rapid information flow, and increasingly plural campus social dynamics. The main issue in this research is how Generation Z students understand, interpret, and express their religion in a digital era that often leads to overlapping religious information. The aim of this research is to describe the forms of religiousness among Generation Z students and to uncover the factors influencing it, both from the digital environment and the campus environment. This research uses a descriptive qualitative approach with a phenomenological method, focusing on the subjective experiences of students in practicing their religiousness. Data is obtained through in-depth interviews with several students from the Religious Studies Program, light observation, and literature studies. The phenomenological approach is used to understand the meanings of religiousness as experienced directly by the students without making normative judgments, allowing the researcher to capture their patterns of religious commitment clearly and authentically. Research findings indicate that the religiousness of Generation Z students is adaptive, selective, and reflective. Social media has become one of the main sources of religious knowledge, but it also presents challenges in the form of information.Non-credible religiosity. On the other hand, the campus environment plays a significant role in shaping moderate, inclusive, and critical religious attitudes through scientific dialogue and cross-background interactions. Overall, the research results affirm that the religiosity of Generation Z develops through a combination of digital experiences and social experiences on campus, thus forming a dynamic pattern of religiosity that meets the demands of the times.